Processing and characterization of PEI/PBT and PEI/PBT/PTFE high-performance polymer blends (2018)
Polymer blending emerged as an attractive strategy to obtain new materials with tailored properties from already existing ones. It has focused mainly on the development of blends from commercial polymers. Fewer works have studied in depth the fabrication of blends from high-performance polymers, since fundamental studies in polymer-polymer interactions are not usually performed with these challenging materials. This work aim to study blends obtained from three high-performance polymers with good flammability characteristics: poly(ether imide) (PEI), poly(butylene terephthalate) (PBT) filled with a flame retardant compound, and poly(tetrafluoroethylene) (PTFE); and presents for the first time, the relationship between processing conditions, viscoelastic properties, interfacial tension, and composition with the morphology and final performance for this kind of systems. Two sets of blends, binary PEI/PBT and ternary (PEI/PBT)/PTFE blend, are prepared by melt processing in an internal mixer. A complete miscibility study is performed from thermal analysis using MDSC and DMA, accompanied by a theoretical approach of the interfacial tension by using the harmonic mean equation. In relation to ternary blends, phase’s interaction is predicted from the Harkin’s spreading coefficient model. Morphological study is contrasted to miscibility results and the distribution of blends constituents is evaluated by SEM and TEM analyses. As blends resulted being partially miscible, the use of selective extraction technique allows us to better evidence the PEI and PBT distribution in binary blends. To evaluate the mechanical performance, tensile tests are performed to Type V samples obtained by injection molding. The thermal stability is studied by TGA and DTG techniques, and flammability tests from a horizon tal burning tests according to the UL-94 standard. The first set of blends is obtained between PEI and PBT, which have notable differences in their processing characteristics. Previous works were found on PEI/PBT blends that mix simultaneously PEI and PBT phases by different solution and melt processing methods. In this work a novel two-step melt processing method to fabricate binary PEI/PBT blends in an internal mixer is proposed. The main processing parameters are defined after the thermal and rheological characterization of pure materials, to obtain binary PEI/PBT blends within the entire compo sition range using the same processing conditions. The second set of blends is obtained with the aim of modify the mechanical properties of PEI/PBT blends by adding PTFE concentrations of 5 wt%, 10 wt%, and 15 wt%. The same two-step melt processing method proposed for binary PEI/PBT blends is used for (PEI/PBT)/PTFE blends fabrication. It is found that PTFE must be added during step 1 in order to enhance phases’ integration during mixing. Ternary blends are obtained for PEI concentrations higher than 50 wt% for the same reason. A complete miscibility study provided information about the phases’ heterogeneity in both, binary and ternary blends. The binary PEI/PBT blends resulted being partially miscible depending on PEI composition, and two groups of blends are identified: PBT-rich blends and PEI-rich blends. Miscibility evaluation by MDSC and DMA reveals that PBT-rich blends are immiscible, since it is no noticed any shift in the glass transition temperatures (Tg) of the pure components. PEI-rich blends on the other hand, exhibit a significant displacements of Tg to higher temperatures suggesting miscibility between PEI and PBT. The study of miscibility in ternary blends, reveals that PTFE does not interfere with the miscibility behavior of PEI and PBT, since there are noticed the same thermal transitions as those for binary blends. Interfacial tension values reveal that all phases are highly immiscible for all possible polymer pairs, due to the no table differences between their polar components. Prediction of phase’s distribution in ternary blends by the spreading coefficient model, reveals there is favored the encapsulation of PTFE phase by PEI when PBT is the matrix. Morphological evaluation of binary PEI/PBT blends is in good agreement to blends microrheology theory proposed by Taylor and Grace. PBT-rich blends exhibit coarse droplets distribution of highly viscous PEI phase, with sub-inclusions of small droplets of low viscous PBT phase. By using the Soxhlet selective extraction technique together with SEM and TEM, it is presented new evidence on the morphological evolution of PBT-rich blends, and we noticed that PBT-rich and PEI-rich blends are separated by an intermediate cocontinuous morphology at even PEI and PBT compositions. PEI-rich blends on the other hand, exhibited tiny droplets of PBT (as small as 120 nm) bonded to PEI matrix through a fibrillar interface, and a new morphology denominated spore-like morphology is presented. In order to validate the addition of PTFE to the PEI phase during step 1 in ternary blends fabrication, we evaluate the morphology formed between PEI/PTFE blends. It is noticed that under these conditions it is favored the distribution of PTFE phase in two major fashions: well-embedded PTFE nano-sized droplets, and debonded PTFE spheres of 1.5 μm of average diameter. SEM and TEM analysis of ternary blends confirm the miscibility study results, and encapsulation of PTFE droplets by PEI phase in ternary blends when PBT is the matrix, is predicted by the spreading coefficient model. Mechanical, thermal, and flame resistance performance is strongly influenced by miscibility and the morphologies obtained in both, binary and ternary blends. The experimental results are discussed in terms of theoretical additivity approaches. In binary bends, the tensile modulus reveal a positive deviation from additivity, and even a synergic contribution is obtained for blends containing 50 wt% and 80 wt% of PEI. The yield strength on the other hand, is strongly affected by phase’s immiscibility and the interfacial adherence between constituents, and a combinatorial deviation from additivity is obtained: negative for PBT rich-blends and positive for PEI-rich blends. In addition, the elongation at break for all blends is compromised by the morphology of PBT-rich blends, and by the densification of PEI-rich blends. The blend with 50 wt% of PEI exhibits the best elongational at break result due to its co-continuous morpholo gy. PTFE phase does not affect PEI/PBT stiffness since any significant variation in tensile modulus values is observed. On the other hand, a progressive decrease in tensile strength with in creasing PTFE concentration caused by the low yielding strength characteristic of PTFE is noticed. The results of elongation at break show that PTFE addition decreases even more the ductility of binary PEI/PBT blends. However, surprising results are found when only 5 wt% of PTFE phase is added to the blends containing 80 wt% of PEI. It is noticed a considerable improve ment of blends ductility due to the highly crystalline PTFE phase inhibits the densification of PEI/PBT blends. On the contrary, PTFE improves substantially PEI/PBT blends thermal stability and flammability, since it enhances blends charring formation.